1994
DOI: 10.33584/jnzg.1994.56.2141
|View full text |Cite
|
Sign up to set email alerts
|

More persistent legumes and grasses for oversown tussock country

Abstract: A grazing trial on oversown tussock country at Tara Hills Research Station, started in 1978 and still continuing, has highlighted short comings of clovers and grasses traditionally used for improvement. In 1984 a wide range of legume and grass germplasm was planted into each of the nine stocking rate/management treatments to identify plant material more persistent than that traditionally used, and investigate specific responses under Extreme (high stocking rate), Optimal (moderate stocking rate and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…These findings are in agreement with Albrecht (2002), who reported that kura clover survived winters in Wisconsin when adjacent alfalfa and red clover fields were damaged. Additionally, after 15 yr of grazing in New Zealand, Allan and Keoghan (1994) reported good survival of kura clover but poor survival of several varieties of birdsfoot trefoil.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with Albrecht (2002), who reported that kura clover survived winters in Wisconsin when adjacent alfalfa and red clover fields were damaged. Additionally, after 15 yr of grazing in New Zealand, Allan and Keoghan (1994) reported good survival of kura clover but poor survival of several varieties of birdsfoot trefoil.…”
Section: Resultsmentioning
confidence: 99%
“…This is a recognized attribute of this species and it was taken into account by reducing the companion grass seed rate for this treatment. There are promising results of its use under extensive grazing from outside Europe (Allan and Keoghan, 1994) where it has outperformed other commonly used legume species (Virgona and Dear, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The use of virtual investigations into hill country farming systems made rapid progress during the 1980s as computer use and computing power increased. A total Suckling 1956;Suckling 1959;Grant et al 1973;Suckling 1975;Dawson & Smith 1976;Smith & Dawson 1977;Grant et al 1978;During et al 1980;Smeaton & Winn 1981;Lambert & Clark 1983;Sheath 1983;Smeaton et al 1984;Allan 1985;Sheath & Rattray 1985;Allan 1992;Smeaton et al 1999;Boom & Sheath 2000;Hodgson et al 2005 Forage Allan et al 1985;Allan & Keoghan 1994;Stevens & Casey 2014Animal Hight 1968Joblin et al 1972;Baker & Carter 1976;Dalton 1976;Rattray 1977;Rattray 1978;Smeaton et al 1979;Rattray 1981;Rattray et al 1982;Smeaton et al 1982;Rattray et al 1983;Smeaton et al 1983;Harris & Clark 1985;Smeaton et al 1986;Journeaux et al 1987;Smeaton et al 1995;Boom & Sheath 1998;Smeaton et al 2000;Fertiliser Clark & Lambert 1982Lambert & Clark 1983;Lambert & Clark 1985;…”
Section: Modelling Researchmentioning
confidence: 99%